The Effect of the Universal Design Model in Learning on the Academic Success of Eighth Grade Students: The Subject of Heredity - Alev Rencüzoğulları; Tolga Saka (e-Kafkas Eğitim Araştırmaları Dergisi)
The aim of this study is to determine the effect of teaching the heredity subject with the Universal Design for Learning (UDL) on students' academic achievement towards science lesson. In addition, during the implementation of this teaching model, it was aimed to determine the effects of computer/tablet, internet availability at home and presence of helpers at home variables on the results. The study was conducted with 73 8th grade students of a public school in Kars in the 2021- 2022 academic year. In the study, two of the four classes were determined as the experimental group and two as the control group. While the lessons in the experimental group were taught according to the plans prepared within the framework of UDL, the control group was taught within the framework of the activities recommended in the curriculum. The data were collected with the 8th Grade Heredity Subject Achievement Test and the Personal Information Form prepared to determine the demographic characteristics of the students. Multi-Factor Analysis of Variance (MANOVA) was used in the analysis of the quantitative data obtained in the study. When the pre-test and post-test scores of the students in the experimental and control groups were compared, it was seen that there was a significant difference in favor of the experimental group. As a result, it was determined that the course taught according to UDL increased the academic achievement of the students the science course, regardless of all these variables. The implementation of the UDL model by teachers in the design of inclusive practices for effective and efficient science education in rural areas is among the recommendations of this research.